2022
DOI: 10.3390/educsci12080539
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Psychometric Properties of Brief COPE in Russian Schoolteachers

Abstract: This study investigates the psychometric properties of brief COPE in Russian schoolteachers. A total of 773 (91% female; M = 43, SD = 9.79) teachers participated in the study. Principal component analysis (PCA) and confirmatory factor analysis (CFA) were applied to assess the psychometric properties of the brief COPE. The Perceived Stress Scale (PSS) was used to assess the construct validity. The main result of the current research is a revised structure for the brief COPE consisting of six sub-scales: «socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A review of 72 studies showed the impact of remote learning (caused by factors including the COVID-19 pandemic) on children's psychological well-being as well as emotional (e.g., stress, anxiety) and behavioral problems 14 . Remote learning is a specific circumstance that creates additional stress, as demonstrated in a number of studies, mainly in adult (student and teacher) samples 15 17 . Diagnostic tools to measure stress and coping strategies in adolescent schoolchildren are needed necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 72 studies showed the impact of remote learning (caused by factors including the COVID-19 pandemic) on children's psychological well-being as well as emotional (e.g., stress, anxiety) and behavioral problems 14 . Remote learning is a specific circumstance that creates additional stress, as demonstrated in a number of studies, mainly in adult (student and teacher) samples 15 17 . Diagnostic tools to measure stress and coping strategies in adolescent schoolchildren are needed necessary.…”
Section: Introductionmentioning
confidence: 99%